2002
DOI: 10.1080/09712119.2002.9706366
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tween 80 on the Enzyme Distribution in Rumen Liquor and on the Growth of Rumen Bacteria and Fungi

Abstract: Ha, J.K., Lee, S.S., Goto

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Fibre degradation in the rumen gets initiated by attachment of fibrolytic microbes with the feed particles, which is an essential pre-requisite (Akin, 1979;Morris and Cole, 1987). In an earlier experiment in our laboratory and results from the other laboratories, it has been shown that fibrolytic enzymes are maximum in the particulate fraction (partially digested fibrous feed particles in the rumen) (Williams et al, 1989;Huhtanen and Khalili, 1992;Agarwal et al, 2000;Ha et al, 2002). Similarly in the present experiment too it has been observed that major portions (>80%) of the total activity of fibrolytic enzymes were present in the particulate fraction, except protease which was absent in this fraction.…”
Section: Resultsmentioning
confidence: 86%
“…Fibre degradation in the rumen gets initiated by attachment of fibrolytic microbes with the feed particles, which is an essential pre-requisite (Akin, 1979;Morris and Cole, 1987). In an earlier experiment in our laboratory and results from the other laboratories, it has been shown that fibrolytic enzymes are maximum in the particulate fraction (partially digested fibrous feed particles in the rumen) (Williams et al, 1989;Huhtanen and Khalili, 1992;Agarwal et al, 2000;Ha et al, 2002). Similarly in the present experiment too it has been observed that major portions (>80%) of the total activity of fibrolytic enzymes were present in the particulate fraction, except protease which was absent in this fraction.…”
Section: Resultsmentioning
confidence: 86%
“…Hussein et al (1995), reported a lower dietary forage level was followed by a greater TAA concentration in the mixed ruminal bacteria. However, previous studies indicated that dietary Tween 80 supplementation appeared to increase the growth of noncellulolytic bacteria, but not of cellulolytic bacteria (Ha et al 2002;Goto et al 2003;Lee et al 2003). However, contrary to LQB, the differences were quantitatively minimal.…”
Section: Archives Of Animal Nutrition 237mentioning
confidence: 92%
“…It has been speculated that increasing milk fat content by NIS supplementation might be related to the influences of NIS on rumen microflora [20] since rumen fermentation products, such as acetate (a primary milk fat precursor) and butyrate, are used by the cow for energy and by the mammary glands to produce milk fat [23]. Moreover, NIS have been shown to have an impact on rumen fermentation and the rumen microbial population [6,24,25,26,27]. On the other hand, our previous study indicated that the proportions of ruminal amino acids, such as valine, phenylalanine and lysine, were affected by the dietary APG supplementation in goats [14].…”
Section: Discussionmentioning
confidence: 99%